Body Surface Area and Baseline Blood Pressure Predict Subclinical Anthracycline Cardiotoxicity in Women Treated for Early Breast Cancer - Kotwinski, Paul; Smith, Gillian; Cooper, Jackie; Sanders, Julie; Ma, Louise; Teis, Albert; Kotwinski, David; Mythen, Michael; Pennell, Dudley J.; Jones, Alison; Montgomery, Hugh (PloS one, 2016)
Anthracyclines are highly effective chemotherapeutic agents which may cause long-term cardiac damage (chronic anthracycline cardiotoxicity) and heart failure. The pathogenesis of anthracycline cardiotoxicity remains incompletely understood and individual susceptibility difficult to predict. We sought clinical features which might contribute to improved risk assessment. Subjects were women with early breast cancer, free of pre-existing cardiac disease. Left ventricular ejection fraction was measured using cardiovascular magnetic resonance before and >12 months after anthracycline-based chemotherapy (>3 months post-Trastuzumab). Variables associated with subclinical cardiotoxicity (defined as a fall in left ventricular ejection fraction of ≥5%) were identified by logistic regression. One hundred and sixty-five women (mean age 48.3 years at enrollment) completed the study 21.7 months [IQR 18.0-26.8] after starting chemotherapy. All received anthracyclines (98.8% epirubicin, cumulative dose 400 [300-450] mg/m2); 18% Trastuzumab. Baseline blood pressure was elevated (≥140/90mmHg, mean 147.3/86.1mmHg) in 18 subjects. Thirty-four subjects (20.7%) were identified with subclinical cardiotoxicity, independent predictors of which were the number of anthracycline cycles (odds ratio, OR 1.64 [1.17-2.30] per cycle), blood pressure ≥140/90mmHg (OR 5.36 [1.73-17.61]), body surface area (OR 2.08 [1.36-3.20] per standard deviation (0.16m2) increase), and Trastuzumab therapy (OR 3.35 [1.18-9.51]). The resultant predictive-model had an area under the receiver operating characteristics curve of 0.78 [0.70-0.86]. We found subclinical cardiotoxicity to be common even within this low risk cohort. Risk of cardiotoxicity was associated with modestly elevated baseline blood pressure-indicating that close attention should be paid to blood pressure in patients considered for anthracycline based chemotherapy. The association with higher body surface area suggests that indexing of anthracycline doses to surface area may not be appropriate for all, and points to the need for additional research in this area.